PENGARUH FRAKSI VOLUME SERAT TEBU TERHADAP KEKUATAN TARIK DAN BENDING KOMPOSIT UNSATURATED POLYESTER-AMPAS KOPI - Yanuar Alditya Nugraha; Dedi Dwi Laksana; imam sholahuddin (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
Bagasse fiber (BF) can be utilized as a reinforcement on composites especially because it is environmentally friendly and comes from renewable resource. In this case, composites use chooped type fibers and manufacturing processes with hand layup method. The volume fraction of unsaturated polyester (UP) as a matrix fixed at 60%, and the fraction of BF and SCG filler varied by 0:40, 10:30, 20:20, 30:10, 40:0. In the application of composite panels, mechanical properties become the main focus in mixing beside to obtaining other characteristics. Addition of spent ground coffee particles (SCG) which decreases the tensile and flexural properties of composites, can be recovered by adding bagasse fiber. The best fraction composition occurred at 10:30 (10BF30SCG60UP), which increased the tensile strength composite (40SCG60UP) by 35.88% and the bending by 14.97%. Eventually, with the cheap, simple method and utilization of industrial waste show the successful experiment to produce stronger and more useful material. Keywords: Bagasse fiber, Composite panel, Mechanical properties.